2016
DOI: 10.1080/10715762.2016.1235787
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol/disulphide homeostasis before and after radical prostatectomy in patients with prostate cancer

Abstract: Thiol groups are important anti-oxidants and essential molecules protecting organism against the harmful effects of reactive oxygen species (ROS). The aim of our study is to evaluate thiol-disulphide homeostasis with a novel recent automated method in patients with localized prostate cancer (PC) before and six months after radical prostatectomy (RP). 18 patients with PC and 17 healthy control subjects were enrolled into the study. Blood samples were collected from the controls subjects and patients before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…Additionally, they noted that the elevated GSH containing compounds is independent of the age of red blood cell 23 . Additionally, in another study demonstrated previous studies which utilized Erel and Neşelioğlu method, found that plasma thiol disulphide homeostasis was increased in degenerative diseases, such as diabetes, obesity, pneumonia, and in the case of asthma, whereas it was reduced in proliferative diseases such as multiple myeloma, renal cell carcinoma, lung cancer, and renal cancer [24][25][26][27][28][29][30] . In this study we could not find any differences between the PV and control groups in terms of the amount of plasma disulphide bonds.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, they noted that the elevated GSH containing compounds is independent of the age of red blood cell 23 . Additionally, in another study demonstrated previous studies which utilized Erel and Neşelioğlu method, found that plasma thiol disulphide homeostasis was increased in degenerative diseases, such as diabetes, obesity, pneumonia, and in the case of asthma, whereas it was reduced in proliferative diseases such as multiple myeloma, renal cell carcinoma, lung cancer, and renal cancer [24][25][26][27][28][29][30] . In this study we could not find any differences between the PV and control groups in terms of the amount of plasma disulphide bonds.…”
Section: Discussionmentioning
confidence: 93%
“…Thiols are organic compounds containing a sulfhydryl group (-SH) which act as physiological free radical scavengers [25]. The total plasma thiols include albumin thiols, other proteins containing free thiol groups and low-molecularweight thiols, [26] such as cysteine and glutathione [27].…”
Section: Introductionmentioning
confidence: 99%
“…thiols, which contain a functional group of sulfhydryls, are potent antioxidant molecules that preserve the organism from the destructive influences of OS damage (Hanikoglu et al 2016). When OS develops, thiol groups in albumin, cysteine, homocysteine, glutathione, as well as other proteins are converted to disulphides.…”
Section: Introductionmentioning
confidence: 99%